2016
DOI: 10.1002/tea.21336
|View full text |Cite
|
Sign up to set email alerts
|

Early elementary students’ understanding of complex ecosystems: A learning progression approach

Abstract: Engaging in systemic reasoning about ecological issues is critical for early elementary students to develop future understanding of critical environmental issues such as global warming and loss of biodiversity. However, ecological issues are rarely taught in ways to highlight systemic reasoning in elementary schools. In this study, we conducted semi‐structured interviews with 44 students from the first through fourth grades. Using an iterative process, we developed an empirically grounded learning progression … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

4
45
1

Year Published

2017
2017
2022
2022

Publication Types

Select...
6

Relationship

1
5

Authors

Journals

citations
Cited by 58 publications
(62 citation statements)
references
References 68 publications
(95 reference statements)
4
45
1
Order By: Relevance
“…Researchers often begin with developing a theoretical LP based on relevant literature. Using the theoretical LP as a guiding framework, they develop assessment tasks (e.g., clinical interview tasks and written assessment tasks) to elicit student thinking (e.g., Hokayem & Gotwals, ). They analyze the assessment data and use the analysis results to redevelop, revise, and refine the LP and associated assessment tasks.…”
Section: Resultsmentioning
confidence: 99%
“…Researchers often begin with developing a theoretical LP based on relevant literature. Using the theoretical LP as a guiding framework, they develop assessment tasks (e.g., clinical interview tasks and written assessment tasks) to elicit student thinking (e.g., Hokayem & Gotwals, ). They analyze the assessment data and use the analysis results to redevelop, revise, and refine the LP and associated assessment tasks.…”
Section: Resultsmentioning
confidence: 99%
“…Unlike many other studies that have examined written assessment data to provide evidence for a LP, our observations were based on pre‐ and post‐instruction, clinical interviews with students (Ginsburg, 1997). This method has been previously used to provide evidence for LP validity in a few studies (e.g., Hokayem & Gotwals, 2016; Plummer, 2014; Wyner & Doherty, 2017). Our method of interpretation consisted of aligning coded interviews with the levels of each construct map.…”
Section: Methodsmentioning
confidence: 99%
“…Gotwals and Songer's (2010) investigation of students' reasoning about food chains revealed variations in how students reason depending on contextual information in the assessment. Hokayem and Gotwals (2016) also found that students were reasoning at different levels on their LP within individual open‐ended questions they used to assess students' thinking about ecosystems. Thus, assigning an individual student to a specific LP level may provide challenges to be monitored in the validation process.…”
Section: Developing and Validating Learning Progressionsmentioning
confidence: 99%
See 1 more Smart Citation
“…Researchers have described learning progressions for physical science topics such as matter (e.g., Hadenfeldt, Neumann, Bernholt, Liu & Parchmann, 2016) and energy (e.g., Neumann, Viering, Boone, & Fischer, 2013), earth science topics such as the water cycle (Forbes, Zangori, & Schwarz, 2015) and climate change (e.g., Breslyn, McGinnis, McDonald, & Hestness, 2016), and life science topics such as genetics (e.g., Todd & Kenyon, 2015) and ecosystems (e.g., Hokayem & Gotwals, 2016). In addition to learning progressions in these content areas, researchers have also described learning progressions for science practices such as argumentation (e.g., Osborne et al, 2016).…”
mentioning
confidence: 99%